Developing customer-centric feedback processes: Case Citycon - Palin, Sofia (My University, 2014)
The work presented in this thesis was commissioned by a real estate company who owns, manages and develops shopping centres in the Nordics and Baltics. Company’s core business is to manage best-in-class shopping centres and offer the best spots for retailers. The work was commissioned because the company wanted to make collecting and utilizing customer feedback more effective and learn to use the customer feedback data in operational development. The research method was qualitative case study because the research findings were utilized according to the case company’s needs. The research part included defining the qualities of the different customer feedback channels and assessing the qualities of different kind of feedback types and feedback channels with respect to best practice literature. To summarize the research findings in the end of the research, the most useful research findings were determined to develop company’s feedback processes. As a consequence, a new operational model for customer feedback and experience management was established based on research findings and industry best practices. In addition to a written report, the thesis developed a new customer feedback system for the company and valuable insights for further development work. The new process will allow the company to gather information efficiently from many channels. It also defines how the feedback is collected, which feedback channels are used and how the information is saved and processed afterwards. With the information available, it can be measured quantitatively, used for monitoring performance and also for sustainable customer experience management.
Keywords: feedback; customer experience; process development; best practices; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|